Burden of urogenital congenital anomalies: findings from the global burden of disease study 2021 - Yue, Yiwei; Zhang, Qian; Li, Ji; Wang, Lei; Guo, Lihua; Sun, Quan (Frontiers in Pediatrics, 2025)
BackgroundUrogenital congenital anomalies (UCAs) are among the most common organ system abnormalities in the neonate. This study employs Global Burden of Disease, Injury, and Risk Factor Study 2021 (GBD 2021) to systematically quantify the global epidemiological burden of UCAs from 1990 to 2021, examining geographic variations and temporal trends.Materials and methodsData were extracted from the GBD 2021. We focused on UCAs-related metrics: prevalence, incidence, deaths, and disability-adjusted life years (DALYs) across 204 countries and territories, grouped into 5 or 21 GBD regions by the socio-demographic index (SDI). Data analysis encompassed relative change calculations, as well as annual percentage change (APC) and average annual percentage change (AAPC), both of which are based on joinpoint regression analysis. The study additionally employed decomposition analysis, frontier analysis and cross-country health inequality analysis. Analyses utilized R version 4.3.1.ResultsFrom 1990 to 2021, the global prevalence of UCAs cases surged by 21%, exceeding 6.34 million, accompanied by an increase in age-standardized rates. Incidence, mortality, and DALYs experienced declines in both absolute figures and age-standardized rates. Gender-specific trends from 1990 to 2021 revealed that females dominated in prevalence, while males had higher mortality and DALYs burden. Regionally, Southern Sub-Saharan Africa exhibited the highest prevalence, while Oceania and East Asia showed significant increases and decreases, respectively. Decomposition analysis of change in prevalence indicated that, globally, population contributed the most to changes in prevalence, followed by aging and epidemiological change. Frontier analysis of 204 countries and regions linked higher SDIs to lower UCAs prevalence. However, unexpected deviations were observed in some high SDI countries, such as Singapore and South Korea. Health inequality analysis revealed that the health inequality in prevalence between high-income and low-income countries decreased in 2021, although the burden became more concentrated in low-income countries.ConclusionOur analysis highlights the intricate relationship between socio-demographic factors and UCAs trends, underscoring the urgent need for targeted and context-specific healthcare interventions. While significant advancements have been made, sustained vigilance and ongoing research remain critical to achieving effective global management of UCAs.